The Great Challenge of Our Time: Awakening to a New Story. (September 2019) - Baring, Anne
In the first part of this article I will explore the reasons for the loss of the Divine Feminine and the powerful mythologies and beliefs which have structured our present view of reality. These have split Nature from Spirit and mind from soul and led to the idea of our dominance of Nature rather than to a caring relationship with it. In the second part I will explore the transformation of this outdated view as our consciousness moves to a new level of understanding and embraces a New Story. The greatest challenge of our time is to heal the split between Spirit and Nature and reconnect our rational mind with our neglected soul.